ANALISIS PROSEDUR PEMBERIAN KREDIT UNTUK MENGURANGI TINGKAT NON PERFORMING LOAN (NPL) PADA BANK SUMSEL BABEL CABANG PEMBANTU PENDOPO LINTANG - SAEKARINI YULIACHTRI; ROSALINA GHAZALI; NURLELA NURLELA; DEWI PUSPA SARI (AKUNTIA JURNAL Jurnal Akuntansi, Terpercaya, Menginspirasi dan Asli, 2020)
This research was conducted at the Bank of South Sumatra Babylon Sub-Branch of Pendopo Lintang with the aim to find out the implementation of credit granting procedures to reduce the occurrence of bad credit. Data analysis method used is qualitative analysis. Qualitative analysis is explained by collecting, compiling, evaluating and interpreting data. The data collection technique used is documentation. The procedure for granting credit to the South Sumatra Bank Babel branch of Pendopo Lintang has carried out the stages of lending in accordance with standards, starting from the stage of submitting a loan application, the stage of investigation and data analysis, and the decision stage on the loan application, the stage of disbursing credit facilities and the Credit Supervision stage and Debtor Development. However, the lack of rigor of analysis in the implementation of lending still has the potential to create the risk of bad credit which ultimately harms the Bank of South Sumatra's Babel Branch of Pendopo Lintang.